World War II, Global Food Crisis and the Grow-More-Food Campaign in Malawi, 1939–1959. Issue 5 (3rd September 2021) - Nkhoma, Bryson G.
ABSTRACT: The outbreak of World War II in 1939 altered the trajectory of food production in Malawi in the last two decades of colonialism. This paper examines the extent to which the World War II and the World Food Crisis that followed shaped peasants' food production in Malawi between 1939 and 1957. It argues that, while the war caused food shortages through the dislocation of labour and foodstuffs, it also altered the production of surplus foodstuffs. Despite its merits, the paper observes, however, that colonial campaign for the peasants to grow more foodstuffs was a 'marriage of convenience' rather than an attempt to improve the food welfare of the peasants. As soon as the food crisis ended, the colonial authority resorted to its old policy of prioritising on cash crops at the expense of food crops. This history sheds new light to rethink 'the second colonial occupation' thesis by arguing that colonial appropriation of African resources in the 1940s and 1950s was complex, dynamic and contested. Foodstuffs laid at the core of rural life such that the colonial state could hardly expropriate them or discourage their excessive production without challenges from the peasants.